A review on flexion angle in high-flexion total knee arthroplasty for indonesian’s need - Darmanto, D.; Novriansyah, R.; Anggoro, P. W.; Ismail, R.; Jamari, J.; Bayuseno, A. P. (Frontiers in Mechanical Engineering, 2022)
Total Knee Arthroplasty (TKA) proposed as an alternative treatment for damaged knee joints of humans is reviewed. The commercial application of TKA can help patients to improve their daily normal activities. Here the high-flex type total knee arthroplasty (High-Flex TKA) is typically designed for the patient’s convenience on which the greater range of motion can be adjusted for extreme activities such as Seiza and Muslim praying. However, the present High-Flex TKAs have not fulfilled the needs of Indonesians for religious activities with a flexion angle of 150°–165°. Therefore, this review aims to examine the flexion range of High-Flex TKAs proposed for the needs of Indonesians. This study is a narrative review, all studies published and reviewed are related to the range of flexion angles on the use of products from many manufacturers and various types that have been used by patients, as well as the development of a CAD-based TKA design. It was proposed in the present study that the flexion angle on High-Flex TKAs may be optimized by thickening the posterior femoral condyle, creating a medial pivot system, and applying a single radius system on the femoral component. Whereas, the tibial insert component could be designed by setting up the posterior tibial slope, and creating a post-cam stabilizer mechanism. Many knowledge gaps related to the population of research objects, lack of research on extreme angles, development of TKA components, are discussed. Further needs of extensive research on TKA in Mongoloid races are anticipated to be introduced for extreme angles and most comprehensive product development for optimization of the flexion angle.